Bentuk Penindasan Sosial Perempuan Pada Novel Wedding Agreement Karya Mia Chuz - Eva Widianingsih (PIKTORIAL : Journal of Humanities, 2021)
This research is a feminist literary criticism of literary works. Regarding feminist literary criticism. This study aims to reveal the position of the female main character, the forms of gender injustice of the female main character and the forms of the female main character's struggle to fight in the novel Wedding Agreement by Mia Chuz. The research method used is a qualitative descriptive method with a feminist literary criticism approach. The data source is the novel Wedding Agreement, while the data are in the form of words, phrases, and sentences. Results Based on data analysis, it was found: 1) The position of female figures includes social status which includes education, career, and status of women. The position of women in society also includes those who are self-sacrificing, independent, and have self-respect. 2) Forms of injustice for women include forced matchmaking, not having the right to choose and counterfeminist actions, mostly psychological violence.3) The form of the struggle of the main female characters against them dares to express their opinions and can make decisions for themselves.